OTU-015 The accuracy and tolerability of magnet assisted capsule endoscopy for the investigation of oesophageal pathology. (8th June 2018) - Beg, Sabina; Card, Tim; Wilkes, Emilie; White, Jonathan; Rahman, Imdadur; Ragunath, Krish
Abstract : Introduction: Gastroscopy (OGD) is the established method for the investigation of oesophageal disease. Magnet Assisted Capsule Endoscopy (MACE) potentially offers a comfortable, patient friendly and community-based alternative to conventional endoscopy. This pilot study aims to explore whether this approach can be used to detect oesophageal pathology. Methods: MACE procedures were carried out using the Mirocam Navi capsule endoscope, which is steerable with the use of an external handheld magnet. A total of 50 participants were enrolled, of which 34 had known pathology, 17 Barrett's Oesophagus (BO), 17 Oesophageal Varices (OV), with 16 controls. Patients underwent the MACE procedure first by a single operator blinded to the indication. The subsequent OGD was performed by a different endoscopist blinded to the MACE findings. Sedation pre-OGD was given as per patient preference. Diagnostic yield, comfort and patient preference between the two modalities were compared. Results: 47 patients undertook both procedures (3 patients were unable to swallow the capsule), with a mean age of 61 years old (range 39–83), M:F of 2.1:1. Participants had a mean BMI of 29.5, with an average chest measurement of 105.3 cms. Three patients were unable to swallow the capsule. Sedation was requested by patients, in addition to throat spray, in 60% of OGDs (median 3 mg midazolam and 50 mcg fentanyl). With the use of the magnet, it was possible to hold the capsule in the oesophagus for a mean duration of 3 mins and 10 s and a maximum of 10 mins and 34 s. A correct real time MACE diagnosis was made in 11/15 patients with OV, 16/16 patients with BO and 15/16 controls. MACE was also able to correctly identify incidental findings, such as oesophagitis, hiatus hernia and as well as an inlet patch. Sensitivity and specificity of diagnosing OV was 73.3% (95%CI: 0.45–0.91) and 96.9% (95%CI: 0.82–1) respectively and in diagnosing BO 100% (95%CI: 0.76–1) and 100% (95%CI: 0.86–1). MACE was considered more comfortable than conventional endoscopy (p<0.0001) with a mean score of 9.2 with MACE compared to 6.7 with OGD, when assessed on a 10-point scale. 78% of patients would prefer to undergo MACE if a further examination was required compared to 0% OGD (22% had no preference). No MACE or OGD related complications occurred. Conclusion: This pilot study demonstrates that MACE is both safe and well tolerated by patients. Accuracy for the diagnosis of BO was high and may therefore have a role in screening for this condition.